Malay cooking method terminologies: understanding and usage / Khairunnisa Mohamad Abdullah … [et al.] - Mohamad Abdullah, Khairunnisa; Mohamad, Rosmaliza; Mohd Zahari, Mohd Salehuddin; Md Sharif, Mohd Sazali (Universiti Teknologi MARA, Kedah, 2014)
There are numerous methods of cooking terminologies that are used in Malay cooking that consist of dry and moist methods. However, Although Malay culinary is very rich in terminologies but some of them are disappearing. The probability of these terminologies will become extinct when the older generation dies and it will no longer be spoken or known by anyone. However, this phenomenon occurs not only among the ordinary youngsters but it also goes to young professional chefs and culinarians. Therefore, this study empirically investigates the level of understanding of Malay cooking methods terminologies and its impact to the usage among the young Malay culinarians in their daily cooking activities. This study used a quantitative approach and respondents were among the young Malay culinarians who are working directly in food industries within the Kelang Valley, Malaysia. The results from descriptive and multiple regression analyses revealed that, the majority of the respondents have a relatively poor understanding on Malay cooking methods terminologies. The finding further proved that the respondents only use a few Malay cooking methods terminologies in their daily cooking activities.